The right to the virtual city: Rural retreatism in open-world video games. (June 2021) - Denham, Jack; Spokes, Matthew
This article uses Lefebvre's spatial triad and his concept of The Right to the City to categorise open-world video games as contested virtual spatial experiences, interconnected with the non-virtual spaces in which they are produced and played and replete with the same spatial, capital forces of alienation to be negotiated and maintained. We use qualitative gameplay data ( n = 15), unpacking players' journeys through Lefebvre's conceived, lived and perceived spaces, to show, respectively, how open-world games can be (1) fundamentally about space, (2) spaces interconnected with the non-virtual world and (3) disruptive spatial experiences. In utilising The Right to the Virtual City and our players' tendency to retreat into the wild spaces of our case study game, Red Dead Redemption 2, we evoke the same alienating forces of commodification and capitalism to which Lefebvre spoke, positioning open-world video games as both contested spatial experiences and opportunities to challenge spatialised inequalities.